Synthesis of cadmium selenide thin films at low-temperature by simple chemical route and their characterization - Hankare, P. P.; Delekar, S. D.; Asabe, M. R.; Chate, P. A.; Bhuse, V. M.; Khomane, A. S.; Garadkar, K. M.; Sarwade, B. D. (Journal of Physics and Chemistry of Solids, 2006)
Crystalline CdSe thin film has been deposited using appropriate precursor solution containing cadmium sulfate octahydrate, tartaric acid, potassium hydroxide, ammonia and sodium selenosulfate. The effect of parameters such as bath composition, deposition temperature, pH of the solution, speed of the rotation and the specificity of complexing agent on growth process is studied. The `as-deposited' CdSe thin film was found to be red in color, specularly reflective and well adherent to the glass substrate. The crystalline phase of the deposited sample was hexagonal wurtzite-type. The analysis of optical absorption data shows energy band gap energy (E-g) 2.01 eV. The morphological study and compositional analysis of film sample have been discussed. The electrical resistivity of CdSe thin film was found to the order of 10(6) Omega cm. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: XRD

Synthesis, characterization of chemically deposited indium selenide thin films at room temperature - Asabe, M. R.; Chate, P. A.; Delekar, S. D.; Garadkar, K. M.; Mulla, Imtiaz S.; Hankare, P. P. (Journal of Physics and Chemistry of Solids, 2008)
Polycrystalline In2Se3 semiconducting thin films were prepared by using relatively simple chemical bath deposition method at room temperature by the reaction between indium chloride, tartaric acid, hydrazine hydrate and sodium selenosulphate in an aqueous alkaline medium. Various preparative conditions of thin film deposition are outlined. The as grown films were found to be transparent, uniform, well adherent and red in color. The films were characterized using X-ray diffraction (XRD), scanning electron microscopy, atomic absorption spectroscopy and energy dispersive atomic X-ray diffraction (EDAX). The XRD analysis of the film showed the presence of polycrystalline nature with hexagonal crystal structure. SEM study revels that the grains are homogenous, without cracks or pinholes and well covers the glass substrate. The optical absorption and electrical conductivity was measured. The direct optical band gap value for the films was found to be of the order of 2.35eV at room temperature and have specific electrical conductivity of the order of 10(-2) (Omega cm)(-1) showing n-type conduction mechanism. The utility of the adapted technique is discussed from the view-point of applications considering the optoelectric and structural data. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Chemical synthesis; Semiconductor

Synthesis and characterization of nickel selenide thin films deposited by chemical method - Hankare, P. P.; Jadhav, B. V.; Garadkar, K. M.; Chate, P. A.; Mulla, Imtiaz S.; Delekar, S. D. (Journal of Alloys and Compounds, 2010)
Nickel selenide thin films have been deposited using chemical bath method on non-conducting glass substrates in a tartarate bath containing nickel sulphate octahydrate, hydrazine hydrate, sodium seleno-sulphate in an aqueous alkaline medium. The grown films were uniform, well adherent and black in color. The films were characterized using X-ray diffraction, scanning electron microscopy, optical absorption and electrical measurements. The nickel selenide thin film revealed polycrystalline nature with hexagonal system. The direct optical band gap of the film was found to be 1.61 eV. Electrical resistivity of film was observed in the order of 10(3) (Omega cm) with p-type conduction mechanism. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Crystal growth; Semiconductors; Thin films; X-ray diffraction